1998
DOI: 10.1590/s0074-02761998000700031
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity induced in mice by F8.1 and F8.2 antigens purified from Schistosoma mansoni eggs

Abstract: Schistosoma mansoni soluble egg antigens (SEA) were fractionated by isoelectric focusing, resulting in 20 components, characterized by pH, absorbance and protein concentration. The higher absorbance fractions were submitted to electrophoresis, and fraction 8 (F8) presented a specific pattern of bands on its isoelectric point. Protein 3 was observed only on F8, and so, it was utilized to rabbit immunization, in order to evaluate its capacity of inducing protective immunity. IgG antibodies from rabbit anti-F8 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Significant levels of protection against homologous challenge infection have been observed with the L3 attenuated by irradiation (Oothuman et al , 1979; Bancroft & Devaney, 1993; Bleiss et al , 2002; Lustigman et al , 2003). Crude or partially purified somatic and secretory antigens have been shown to provide partial protection against parasitic helminth infection (Schallig & Van Leeuwen, 1997; Ferreira et al , 1998; Abdel Rahman et al , 2005). Protection studies using partially purified antigens of animal filariids revealed marginally better efficacy using various methods of purification (Storey & Mettias, 1980; Sumati et al , 1990; Dikshit & Misra, 1994; Dixit et al , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Significant levels of protection against homologous challenge infection have been observed with the L3 attenuated by irradiation (Oothuman et al , 1979; Bancroft & Devaney, 1993; Bleiss et al , 2002; Lustigman et al , 2003). Crude or partially purified somatic and secretory antigens have been shown to provide partial protection against parasitic helminth infection (Schallig & Van Leeuwen, 1997; Ferreira et al , 1998; Abdel Rahman et al , 2005). Protection studies using partially purified antigens of animal filariids revealed marginally better efficacy using various methods of purification (Storey & Mettias, 1980; Sumati et al , 1990; Dikshit & Misra, 1994; Dixit et al , 2006).…”
Section: Introductionmentioning
confidence: 99%